2020
DOI: 10.18778/1733-8077.16.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Aspects of Social Research: Old Concerns in the Face of New Challenges and Paradoxes. A Reflection from the Field of Biographical Method

Abstract: The paper deals with the ethical aspects of the research process and contemporary changes in this field, which make the discussion on ethical dilemmas and concerns more dynamic and varied. Although in natural science and social sciences one can find a common ground related to the most general ethical principles. In the article I refer primarily to the social sciences. The article discusses three aspects affecting the dynamics of ethical discussions: the development of research in the field of natural sciences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As a result, our scholarly consultation with recent publications on this ethical quandary provided direction (cf. Kaźmierska, 2020;Lapadat, 2017). Kaźmierska (2020:118) questions whether biographical researchers, in the social sciences, should be equally worried about "old ethical concerns in the face of new challenges and paradoxes".…”
Section: Figure 1: the Building Blocks Of Collaborative Autoethnographymentioning
confidence: 99%
“…As a result, our scholarly consultation with recent publications on this ethical quandary provided direction (cf. Kaźmierska, 2020;Lapadat, 2017). Kaźmierska (2020:118) questions whether biographical researchers, in the social sciences, should be equally worried about "old ethical concerns in the face of new challenges and paradoxes".…”
Section: Figure 1: the Building Blocks Of Collaborative Autoethnographymentioning
confidence: 99%
“…The more standardised the interview, the more often the power relationship is unequal between the researchers and the interviewees. Currently, it is one of the important threads in the discussion in the field of ethics (Mauthner, 2019; Kaźmierska, 2020), especially regarding posthuman ethics, where it is suggested that the role difference between the researcher and the research subject should be completely abolished (Denzin and Giardina, 2007: 20). We are not in favour of such a radical solution.…”
Section: From Research Practice To Defining the Story And Its Authormentioning
confidence: 99%
“…From the moment an account is submitted in a publicly available archive, it is the institution's task to verify the people using the resource in such a way as to minimise the risk of unethical use. The problem is certainly weighty, and the process of sharing and disseminating requires a great deal of sensitivity and mindfulness from all parties involved and ethical tension remains (Gałęziowski, 2019;Kaźmierska, 2018Kaźmierska, , 2020.…”
Section: Archivingmentioning
confidence: 99%